ASSOCIATION BETWEEN SARRCOPENIA AND COMPREHENSIVE GERIATRIC CHARACTERISTICS IN OLDER ADULTS (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of sarcopenia in older adults according to AWGS (2019) and its association with comprehensive geriatric characteristics.Subjects and methods: Cross-sectional study of 323 patients aged ³ 60 years old at the National Geriatric Hospital from September 2023 to August 2024. Participants were assessed for geriatric conditions including nutritional status (MNA-SF), functional status (instrumental activities of daily living - IADL, and basic activities of daily living - ADL), physical activity level (IPAQ-SF), fall history, fall risk (21-item fall risk index), frailty (clinical frailty scale), depression, and comorbidity burden (Charlson comorbidity index).Results: The prevalence of sarcopenia based on the AWGS (2019) criteria in older adults was 37.8%. Malnutrition or risk of malnutrition, ADL dependency, IADL dependency, low IPAQ-SF, high fall risk, frailty, depression, and high Charlson comorbidity scores were all associated with sarcopenia. Multivariate logistic regression analysis revealed that age 70-79 years, living alone, overweight obese, and ADL dependency were independent factors associated with sarcopenia.Conclusion: Sarcopenia is closely related to multiple comprehensive geriatric characteristics, particularly nutritional status, daily functional capacity, physical activity, fall risk, frailty, depression, and comorbidities. Routine geriatric assessment should integrate sarcopenia screening to enable early detection and timely intervention.
Keywords: Sarcopenia, comprehensive geriatric characteristics, older adults.